Maps of Time: Rhetoric of Place in Ulysses, by James Joyce - Cunha, Gualter (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Ulysses’ episodes feature a correspondence with figures or events in the history of the Odyssey, with the sole exception of the central episode, “Wandering Rocks”, whose title alludes to a possible voyage by Odysseus that does not take place. As for Odysseus in Homer, also for Joyce’s main characters (Leopold and Molly Bloom and Stephen Dedalus) “Wandering Rocks” designates a non-episode, as their participation in it is (almost) non-existent. Without a Homeric parallelism “Wandering Rocks” has thus for sole reference the city of Dublin, where a lot of characters move and meet and who all together only relate to each other by sharing the same geographical space. In this article I try to show the existence of rhetorical similitudes between the use of Dublin’s map (or geography) in the representation of community in “Wandering Rocks” and the use of the character’s interiority (or psychology) in the representation of consciousness in many of the other episodes of the novel.